Composition for film layers

By using metallocene-catalyzed medium-density polyethylene and mixed plastic-polyethylene recycling blends in polyethylene recovery materials, the problem of insufficient performance of recycling plastic materials is solved, and good mechanical and optical properties of high content recycling materials are achieved , meet consumer needs.

CN119173571APending Publication Date: 2024-12-20北欧化工公司
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
CN202380039919.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-12
Filing Date
2023-05-09
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing recycled plastic materials have shortcomings in terms of mechanical properties, stiffness and optical properties. In particular, the quality of recycled polyethylene materials is lower than that of the original materials, which is difficult to meet consumer requirements and difficult to simultaneously improve their impact strength and haze.

Method used

Using metallocene-catalyzed medium density polyethylene (MDPE) combined with mixed plastic-polyethylene recovery blend (PERB), the density, flow rate ratio and molecular weight distribution of the composition are improved through specific polymer design and process conditions. , to form a film with good mechanical properties and improved optical properties.

Benefits of technology

In the case of high content of recycled materials, it is achieved to provide a film with good impact resistance, stiffness and optical performance balance, meet consumer needs and improve the quality of recycled plastics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005129635010000121
    Figure BDA0005129635010000121
  • Figure BDA0005129635010000131
    Figure BDA0005129635010000131
  • Figure BDA0005129635010000132
    Figure BDA0005129635010000132
Patent Text Reader

Abstract

A composition comprising a metallocene catalyzed medium density polyethylene (MDPE) and a mixed plastic-polyethylene recovery blend, the use of the composition in film applications and a film comprising the polymer composition of the invention.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a composition comprising metallocene-catalyzed medium density polyethylene (MDPE) and mixed plastic-polyethylene recycled blend (PERB), the use of the composition in film applications and films comprising the polymer composition of the present invention.

[0002] Polyolefins, especially polyethylene and polypropylene, are increasingly consumed in large quantities in a wide range of applications including packaging of food and other goods.

[0003] Polyethylene-based materials are a particular problem, as these are widely used in packaging. Considering the huge amounts of waste collected compared to the amount of waste recycled into the stream, there is still great potential for the intelligent reuse of plastic waste streams and for the mechanical recycling of plastic waste.

[0004] Therefore, it is important to form a circular economy that gives plastic waste a second life, i.e. recycling it. This not only prevents plastic waste from remaining in the environment, but also restores its value.

[0005] In addition, the European Commission confirmed in 2017 that it would focus on plastic production and use. The EU's goals are: 1) by 2025, at least 55% of all plastic packaging in the EU should be recycled; 2) by 2030, all plastic packaging on the EU market should be reusable or easily recyclable. This has prompted brand owners and plastic converters to seek solutions using recyclables or a mix of virgin / recyclables.

[0006] Therefore, incorporating polymers obtained from waste into the manufacture of new products is becoming increasingly important, i.e. where waste plastics, such as post-consumer recyclate (PCR), can be transformed into a resource for new plastic products. Thus, environmental and economic aspects can be combined when recycling and reusing waste plastic materials.

[0007] However, recycled plastics are often of lower quality than virgin plastics due to degradation, contamination and mixing of different plastics.

[0008] In addition, compositions containing recycled polyolefin materials generally have properties that are much worse than those of virgin materials, unless the amount of recycled polyolefin added to the final composition is extremely low. For example, such materials generally have limited impact strength and poor mechanical properties, and therefore, they cannot meet consumer requirements.

[0009] Mixing recycled plastic with virgin plastic is a common practice to improve the quality of recycled plastic.

[0010] For example, EP 3838984 A1 describes blends of LDPE recyclates (e.g. NAV 102 from Ecoplast) with Ziegler-Natta catalyzed LLDPE or MDPE for wire and cable applications. The amount of recyclates added is 4.0 to 35.0 wt%, based on the total composition.

[0011] WO 2020 / 207940 describes a multilayer collation shrink film having good optical surface layer properties, good shrink properties and a good balance between holding power and cold shrink properties.

[0012] Core layer B was 70.0 wt% recycled LDPE and 30.0 wt% Ziegler-Natta catalyzed terpolymer (ie, FX1002) based on the blend.

[0013] Film properties such as stiffness, toughness and haze are not mentioned at all.

[0014] Based on this, it is an object of the present invention to provide a polyethylene-based composition allowing the use of recycled LDPE, which can be used to produce films with good properties, especially good mechanical properties such as impact resistance and improved optics, especially haze, and an improved balance between stiffness, impact resistance and optics, especially haze.

[0015] Furthermore, it should be possible to add higher amounts of recyclables to the composition.

[0016] The present inventors have now discovered that blends of metallocene-catalyzed medium density polyethylene (MDPE) with a specific polymer design and a major portion of LDPE recyclate (i.e. a mixed plastic-polyethylene recycled blend) provide films with an improved balance between stiffness, impact resistance and optics (i.e. haze). Summary of the invention

[0017] The present invention therefore relates to a composition comprising

[0018] (I) 1.0 to 49.0 wt% of a metallocene-catalyzed medium density polyethylene (MDPE), based on the total weight of the composition, wherein the metallocene-catalyzed MDPE has

[0019] 932 to 955 kg / m 3 Density within range (ISO 1183);

[0020] MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 0.1 to 2.0 g / 10 min,

[0021] MFR in the range of 10.0 to 40.0 g / 10 min 21(190℃, 21.6kg, ISO 1133),

[0022] Ratio MFR in the range of 20.0 to 60.0 21 / MFR2(FRR)

[0023] Mw / Mn (MWD) in the range of 2.5 to 7.0, and

[0024] A ratio FRR / MWD in the range of 7.5 to 11.0; and

[0025] (II) 51.0 to 99.0 wt% of a mixed plastic-polyethylene recycled blend (PERB), based on the total weight of the composition, having

[0026] 0.1 to 1.2 g / 10min MFR2 (ISO 1133, 2.16 kg, 190°C),

[0027] 910 to 945 kg / m 3 The density and

[0028] 80.0 to 96.0 wt% of the total amount of ethylene units (C2 units) measured by NMR of the d2-tetrachloroethylene soluble fraction,

[0029] The total amount of C2 units is based on the total weight of the monomer units in the mixed plastic-polyethylene blend (PERB) and is calculated according to the quantitative 13 C{1H}NMR measurement method is used to measure,

[0030] The components (I) and (II) of the composition together constitute up to 100 wt%.

[0031] Unexpectedly, such compositions provide films with an improved balance between stiffness, impact, and optics, ie, haze.

[0032] Therefore, the present invention further relates to a film comprising at least one layer comprising the composition described above.

[0033] The specific design of the metallocene catalyzed medium density polyethylene (MDPE) thus allows for the addition of more recyclables, ie more than 50 wt% of the composition, and still provides a film with a good balance of impact / stiffness and optics.

[0034] definition

[0035] Where the term "comprising" is used in the present description and claims, it does not exclude other, not specifically stated, elements of major or minor functional importance. For the purposes of the present invention, the term "consisting of" is considered to be a preferred embodiment of the term "comprising". If a group is defined hereinafter as comprising at least a certain number of embodiments, this is also to be understood as disclosing the group, which preferably consists only of these embodiments.

[0036] Whenever the terms "including" or "having" are used, these terms are meant to be equivalent to "comprising" as defined above.

[0037] When an indefinite or definite article is used when referring to a singular noun, for example "a", "an" or "the", this includes a plural of that noun unless otherwise stated.

[0038] Metallocene-catalyzed medium density polyethylene (MDPE) is defined in the present invention as a medium density polyethylene produced in the presence of a metallocene catalyst.

[0039] For the purposes of the present invention, "medium density polyethylene (MDPE) comprising a polyethylene component (A) and a polyethylene component (B)" means that the MDPE is produced in at least a two-step sequential polymerization process, wherein component (A) is produced first and then, in a subsequent polymerization step, component (B) is produced in the presence of component (A) to produce the MDPE, or vice versa, i.e. component (B) is produced first and then, in a subsequent polymerization step, component (A) is produced in the presence of component (B) to produce the MDPE.

[0040] MDPE produced in a multistage process is also known as an "in-situ" blend or a "reactor" blend. The resulting final product consists of an intimate mixture of polymers from two or more reactors whose different molecular weight distribution curves together form a molecular weight distribution curve with a broad maximum or two or more maxima, i.e., the final product is a multimodal polymer mixture.

[0041] In the context of medium density polyethylene (MDPE), the term "multimodal" refers herein to the multimodality of the melt flow rate (MFR) of at least two ethylene polymer components, i.e. the two ethylene polymer components have different MFR values. The multimodal medium density polyethylene may additionally or alternatively have multimodality between the two polyethylene components with respect to one or more other properties (such as density, comonomer type and / or comonomer content), which will be described hereinafter.

[0042] For the purpose of this specification and the claims that follow, the term "mixed plastics - polyethylene recycled blend (PERB)" means a polymer material comprising, besides other polymer components of any nature, mainly units derived from ethylene. Such polymer components may be derived, for example, from monomer units derived from α-olefins (e.g. propylene, butene, hexene, octene, etc.), styrene derivatives (e.g. vinyl styrene), substituted and unsubstituted acrylic acid esters, substituted and unsubstituted methacrylic acid esters.

[0043] The polymer material can be quantitatively 13 C{1H}NMR measurements were performed to identify the presence of 2% 2H in mixed plastic polyethylene compositions. The quantitative 13 In C{1H}NMR measurements, the different units in the polymer chain can be distinguished and quantified. These units are ethylene units (C2 units), units with 3, 4 and 6 carbon atoms, and units with 7 carbon atoms.

[0044] Therefore, the unit having 3 carbon atoms (C3 unit) can be distinguished as isolated C3 units (isolated C3 units) and continuous C3 units (continuous C3 units) in the NMR spectrum, which indicates that the polymer material contains a propylene-based polymer. These continuous C3 units can also be identified as iPP units.

[0045] Units with 3, 4, 6 and 7 carbon atoms describe in the NMR spectrum units derived from two carbon atoms in the polymer backbone and short side chains or branches of 1 carbon atom (isolated C3 units), 2 carbon atoms (C4 units), 4 carbon atoms (C6 units) or 5 carbon atoms (C7 units).

[0046] Units having 3, 4 and 6 carbon atoms (separate C3, C4 and C6 units) can be derived from incorporated comonomers (propylene, 1-butene and 1-hexene comonomers) or from short chain branches formed by free radical polymerization.

[0047] Units with 7 carbon atoms (C7 units) can be clearly attributed to mixed plastics - polyethylene primary recycled blends (PERBs) since they cannot be derived from any comonomer. 1-Heptene monomer is not used in the copolymerization. Instead, C7 units represent the presence of LDPE, which is specific to recyclates. It has been found that the amount of C7 units in LDPE resins is always within different ranges. Therefore, by quantifying 13 The amount of C7 units measured by C{1H} NMR measurement can be used to calculate the amount of LDPE in the polyethylene composition.

[0048] Therefore, the amounts of continuous C3 units, separated C3 units, C4 units, C6 units and C7 units are quantified as follows 13 The LDPE content is measured by C{1H}NMR measurement, while the LDPE content is calculated from the amount of C7 units as described below.

[0049] The total amount of ethylene units (C2 units) is due to units in the polymer chain without short side chains of 1 to 5 carbon atoms and in addition to units due to LDPE (ie units with longer side chain branches of 6 or more carbon atoms).

[0050] Traditionally, other components may be present, such as fillers, including organic and inorganic fillers, such as talc, chalk, carbon black, and other pigments, such as TiO2, as well as paper and cellulose. In a particular and preferred embodiment, the waste stream is a consumer waste stream, such a waste stream can be derived from a conventional collection system, such as the collection system implemented in the European Union. The post-consumer waste is characterized by a limonene content of 0.1 to 500 mg / kg (determined by the standard addition method using solid phase microextraction (HS-SPME-GC-MS)).

[0051] In the context of the present invention, the term "natural" means that the components have natural colors. This means that no pigments (including carbon black) are included in the components of the mixed plastic-polyethylene recycled blend of the present invention. DETAILED DESCRIPTION

[0052] The composition of the present invention comprises

[0053] (I) 1.0 to 49.0 wt%, preferably 10.0 to 45.0 wt%, more preferably 20.0 to 40.0 wt% of a metallocene-catalyzed medium density polyethylene (MDPE), and

[0054] (II) 51.0 to 99.0 wt%, preferably 55.0 to 90.0 wt%, more preferably 60.0 to 80.0 wt% of a mixed plastic-polyethylene recycled blend (PERB).

[0055] The amounts of (I) and (II) added together are up to 100.0 wt%.

[0056] (I) Metallocene-catalyzed medium density polyethylene (MDPE)

[0057] It has been found that the metallocene-catalyzed medium density polyethylene according to the present invention provides an improved material for film applications which, when added to mixed plastics-polyethylene recycled blends (PERBs), combines very good mechanical properties, such as tensile modulus, good toughness, such as dart drop impact strength, and excellent optical properties, such as haze.

[0058] The metallocene-catalyzed MDPE used in accordance with the present invention has a temperature range of 932 to 955 kg / m 3 , preferably between 933 and 950 kg / m 3 , more preferably 935 to 945 kg / m 3 Density within the range (ISO 1183).

[0059] The MFR2 (190°C, 2.16 kg, ISO 1133) of the metallocene-catalyzed MDPE is in the range of 0.1 to 2.0 g / 10 min, preferably 0.2 to 1.5 g / 10 min, more preferably 0.3 to 1.2 g / 10 min, even more preferably 0.4 to 1.0 g / 10 min.

[0060] MFR of metallocene-catalyzed MDPE 21 (190°C, 21.6 kg, ISO 1133) is in the range of 10.0 to 40.0 g / 10 min, preferably in the range of 15 to 38.0 g / 10 min, more preferably in the range of 18.0 to 35.0 g / 10 min, most preferably in the range of 20.0 to 33.0 g / 10 min.

[0061] The metallocene-catalyzed MDPE used according to the present invention also has an MFR in the range of 20.0 to 60.0, more preferably in the range of 22.0 to 58.0, more preferably in the range of 25.0 to 55.0. 21 / MFR2 flow rate ratio (FRR).

[0062] Furthermore, the metallocene-catalyzed MDPE has a molecular weight distribution (MDPE) in the range of 2.5 to 7.0, preferably 2.8 to 6.8, more preferably 3.0 to 6.5.

[0063] The metallocene-catalyzed MDPE used according to the present invention has a FRR / MWD ratio in the range of 7.5 to 11.0, preferably 7.8 to 10.5, more preferably 8.0 to 10.0.

[0064] Furthermore, the metallocene-catalyzed MDPE used according to the present invention may have one or more or all of the properties described below:

[0065] Weight average molecular weight Mw

[0066] The weight average molecular weight Mw of the metallocene-catalyzed MDPE is at least 100,000 g / mol, preferably in the range of 109,000 to 150,000 g / mol, more preferably 109,000 to 130,000 g / mol, still more preferably 1,090,000 to 120,000 g / mol.

[0067] Z-average molecular weight Mz

[0068] The z-average molecular weight Mz may be in the range of 215,000 to 400,000 g / mol, preferably 230,000 to 380,000 g / mol, more preferably 250,000 to 350,000 g / mol.

[0069] Mz / Mw ratio

[0070] The Mz / Mw ratio may be in the range of 2.0 to 4.0, preferably 2.2 to 3.5, more preferably 2.3 to 3.2.

[0071] FRR / (Mz / Mw) ratio

[0072] The FRR / (Mz / Mw) ratio may be in the range of 11.5 to 20.0, preferably 11.8 to 19.0, more preferably 12.0 to 18.5.

[0073] The metallocene-catalyzed MDPE may contain additives and / or fillers.

[0074] Optional additives and fillers and the amounts used are conventional in the field of film applications. Examples of such additives are, inter alia, antioxidants, processing stabilizers, UV stabilizers, pigments, fillers, antistatic additives, antiblocking agents, nucleating agents, acid scavengers and polymer processing aids (PPAs).

[0075] Implementation (I)

[0076] In a preferred embodiment, namely embodiment (I), the metallocene-catalyzed MDPE comprises at least (i) 30 to 70 wt% of a polyethylene component (A) with a density of 950 to 980 kg / m 3 In the range of 2.0 to 500 g / 10 min, MFR2 (190°C, 2.16 kg, ISO 1133) is 2.0 to 500 g / 10 min; and

[0077] (ii) 30 to 70 wt% of a polyethylene component (B), relative to the total weight of the MDPE, having a molecular weight of 900 to 925 kg / m 3 Polyethylene with a density in the range of 0.0001 to 1.0 g / 10 min and an MFR2 (190° C., 2.16 kg, ISO 1133).

[0078] Thus, in the metallocene-catalyzed MDPE, the weight ratio of polyethylene component (A) to polyethylene component (B) is in the range of 30:70 to 70:30, preferably 35:65 to 65:35, more preferably 40:60 to 60:40. In some embodiments, the ratio may be 35 to 50 wt% of polyethylene component (A) to 50 to 65 wt% of polyethylene component (B), such as 40 to 50 wt% of component (A) to 50 to 60 wt% of component (B), wherein the wt% values ​​are relative to the total weight of the metallocene-catalyzed MDPE.

[0079] In a particularly preferred embodiment, the wt% values ​​of components (A) and (B) add up to at most 100%.

[0080] In this embodiment (I), the polyethylene components (A) and / or (B) may be homopolymers or ethylene copolymers.

[0081] Preferably, the MDPE may have two copolymer components or one copolymer component and one homopolymer component, whereby preferably both components are ethylene copolymers, or the polyethylene component (A) is a homopolymer and the polyethylene component (B) is a copolymer, or vice versa (the polyethylene component (A) is a copolymer and the polyethylene component (B) is a homopolymer). More preferably, the polyethylene component (A) is a homopolymer and the polyethylene component (B) is a copolymer.

[0082] For the purposes of the present invention, a polyethylene homopolymer is a polymer comprising at least 99.0 wt%, in particular at least 99.5 wt% of ethylene monomer units. Thus, a polyethylene homopolymer may contain up to 1.0 wt%, but preferably only up to 0.5 wt%, for example up to 0.2 wt% or even only up to 0.1 wt% of comonomer units.

[0083] In one embodiment of the present invention, the amount of comonomer in the polyethylene homopolymer component is 13 C-NMR was undetectable.

[0084] Preferably, polyethylene component (B) is composed of a single ethylene copolymer or a single ethylene homopolymer, more preferably composed of a single ethylene copolymer. Polyethylene component (A) can be composed of a single ethylene homopolymer or copolymer. Alternatively, polyethylene component (A) can be an ethylene polymer mixture comprising a first ethylene polymer portion (A-1) and a second ethylene polymer portion (A-2) (e.g., composed thereof), wherein the two portions are either homopolymers or copolymers. Polyethylene component (A) can be unimodal or multimodal. In the case where polyethylene component (A) is an ethylene copolymer mixture, preferably the comonomers in the first and second ethylene copolymer portions are identical.

[0085] Preferred ethylene copolymers use α-olefins (e.g., C3-12 α-olefins) as comonomers. Examples of suitable α-olefins include 1-butene, 1-hexene, and 1-octene. 1-Butene and 1-hexene are particularly preferred comonomers.

[0086] More preferably, the polyethylene component (A) is an ethylene homopolymer and the polyethylene component (B) is an ethylene-1-hexene copolymer.

[0087] The MFR2 of the polyethylene component (A) is preferably in the range of 10 to 400 g / 10 min, more preferably 50 to 300 g / 10 min, even more preferably 100 to 200 g / 10 min.

[0088] The density of the polyethylene component (A) is preferably in the range of 955 to 975 kg / m 3 , preferably 960 to 972 kg / m 3 , even more preferably 962 to 970 kg / m 3 within the range.

[0089] It is further preferred that the polyethylene component (A) consists of two fractions, namely a first ethylene polymer fraction (A-1) and a second ethylene polymer fraction (A-2), preferably consists of a first ethylene homopolymer fraction (A-1) and a second ethylene homopolymer fraction (A-2).

[0090] It is possible to produce fraction (A-1) first and then, in a subsequent reactor, produce fraction (A-2) in the presence of fraction (A-1), or vice versa, i.e., produce fraction (A-2) first and then, in a subsequent reactor, produce fraction (A-1) in the presence of fraction (A-2). Preferably, fraction (A-1) is produced first.

[0091] The MFR2 and / or density of fractions (A-1) and (A-2) may be the same or may be different from each other.

[0092] Therefore, the MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer part (A-1) is preferably in the range of 5.0 to 100.0 g / 10 min, preferably 10.0 to 80.0 g / 10 min, more preferably 15.0 to 50.0 g / 10 min, even more preferably 20.0 to 40.0 g / 10 min.

[0093] The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer portion (A-2) is preferably in the range of 100.0 to 1500.0 g / 10 min, preferably 200.0 to 1200.0 g / 10 min, more preferably 300.0 to 1000.0 g / 10 min, and most preferably 500.0 to 800.0 g / 10 min.

[0094] Preferably, the MFR2 of fraction (A-2) is higher than the MFR2 of fraction (A-1).

[0095] The density of the ethylene polymer portion (A-1) is preferably in the range of 945 to 970 kg / m 3 , preferably 950 to 965 kg / m 3 , even more preferably 952 to 962 kg / m 3 within the range.

[0096] The density of the ethylene polymer portion (A-2) is 960 to 980 kg / m 3 , more preferably 965 to 980 kg / m 3 , even more preferably 970 to 978 kg / m 3 within the range.

[0097] Preferably, the density of fraction (A-2) is higher than the density of fraction (A-1).

[0098] The MFR2 of the polyethylene component (B) is preferably in the range of 0.0005 to 0.8 g / 10 min, more preferably 0.001 to 0.5 g / 10 min, even more preferably 0.002 to 0.1 g / 10 min.

[0099] The density of the polyethylene component (B) is preferably in the range of 905 to 920 kg / m 3 , more preferably 908 to 918 kg / m 3 , even more preferably 910 to 916 kg / m 3 within the range.

[0100] The metallocene-catalyzed MDPE of embodiment (I) may be produced by polymerizing with a metallocene catalyst system using conditions that produce a multimodal (eg, bimodal) polymer product.

[0101] Thus, the metallocene-catalyzed MDPE of embodiment (I) may be produced in a two-stage process, preferably comprising a slurry reactor (loop reactor), wherein the slurry (loop) reactor is connected in series with a gas phase reactor (GPR), whereby the polyethylene component (A) or the polyethylene component (B) is produced in the loop reactor, and then the other ethylene polymer component is produced in the GPR in the presence of the first produced ethylene polymer component to produce the metallocene-catalyzed MDPE, preferably, the polyethylene component (A) is produced in the loop reactor and the polyethylene component (B) is produced in the GPR in the presence of the polyethylene component (A) to produce the metallocene-catalyzed MDPE.

[0102] In case the polyethylene component (A) of the metallocene-catalyzed MDPE consists of ethylene polymer fractions (A-1) and (A-2), the metallocene-catalyzed MDPE may be produced in a three-stage process, which preferably comprises a first slurry reactor (loop reactor 1), wherein the first slurry loop reactor is connected in series to a further slurry reactor (loop reactor 2), such that the first ethylene polymer fraction (A-1) produced in loop reactor 1 is fed to loop reactor 2, where the second ethylene polymer fraction (A-2) is produced in the presence of the first fraction (A-1). Fraction (A-1) may be produced first and then, in a subsequent reactor, fraction (A-2) is produced in the presence of fraction (A-1), or vice versa, i.e., fraction (A-2) is produced first and then, in a subsequent reactor, fraction (A-1) is produced in the presence of fraction (A-2). Preferably, fraction (A-1) is produced first.

[0103] The reaction conditions of the loop reactor may be used as described in Embodiment (II) below.

[0104] Therefore, the loop reactor 2 is connected in series to a gas phase reactor (GPR) such that the polyethylene component (A) leaving the second slurry reactor is fed to the GPR to produce a trimodal polyethylene copolymer. In this case, the reaction conditions in the two slurry reactors are selected such that products different in MFR and / or density are produced in the two slurry reactors.

[0105] The third polymerization stage is a gas phase polymerization step, ie carried out in a gas phase reactor. Any suitable gas phase reactor known in the art may be used, such as a fluidized bed gas phase reactor.

[0106] For gas phase reactors, the reaction temperature used is usually 60-115° C. (e.g. 70-110° C.), the reactor pressure is usually in the range of 10-25 bar, and the residence time is usually 1-8 hours. The gas used is usually a non-reactive gas, such as nitrogen or a low boiling hydrocarbon, such as propane and a monomer (e.g. ethylene).

[0107] A chain transfer agent, such as hydrogen, is usually added to the third polymerization stage.

[0108] Such processes are described inter alia in WO 2016 / 198273, WO 2021009189, WO 2021009190, WO 2021009191 and WO 2021009192. Full details of how to prepare suitable multimodal polymers can be found in these references.

[0109] A suitable process is the Borstar PE process or the Borstar PE 3G process.

[0110] Therefore, the metallocene-catalyzed MDPE according to embodiment (I) of the present invention is preferably produced in a loop-loop-gas phase cascade.Such a polymerization step may be preceded by a prepolymerization step.

[0111] The purpose of prepolymerization is to polymerize a small amount of polymer onto the catalyst at low temperature and / or low monomer concentration. By prepolymerization, the performance of the catalyst in slurry can be improved and / or the properties of the final polymer can be changed. The prepolymerization step is preferably carried out in slurry. Therefore, the prepolymerization step can be carried out in a loop reactor.

[0112] Then, the prepolymerization is preferably carried out in an inert diluent, which is generally a hydrocarbon diluent, such as methane, ethane, propane, n-butane, isobutane, pentane, hexane, heptane, octane, etc., or a mixture thereof. Preferably, the diluent is a low-boiling hydrocarbon having 1 to 4 carbon atoms or a mixture of these hydrocarbons.

[0113] The temperature in the prepolymerization step is usually from 0 to 90°C, preferably from 20 to 80°C, more preferably from 45 to 75°C.

[0114] The pressure is not critical and is generally 1 to 150 bar, preferably 40 to 80 bar.

[0115] The amount of monomer is usually such that 0.1 to 1000 grams of monomer are polymerized per gram of solid catalyst component in the prepolymerization step. As known to those skilled in the art, the catalyst particles recovered from the continuous prepolymerization reactor do not all contain the same amount of prepolymer. On the contrary, each particle has its own characteristic amount, which depends on the residence time of the particle in the prepolymerization reactor. Because some particles stay in the reactor for a relatively long time, and some stay for a relatively short time, the amount of prepolymer on different particles is also different, and some single particles may contain the amount of prepolymer beyond the above range. However, the average amount of prepolymer on the catalyst is usually within the above range.

[0116] As is known in the art, the molecular weight of the prepolymer can be controlled by hydrogen.In addition, antistatic additives can be used to prevent the particles from sticking to each other or to the reactor walls, as disclosed in WO-A-96 / 19503 and WO-A-96 / 32420.

[0117] When there is a prepolymerization step, the catalyst components are preferably all introduced into the prepolymerization step. However, when the solid catalyst component and the cocatalyst can be fed separately, it is possible that only a part of the cocatalyst is introduced into the prepolymerization stage, while the rest is introduced into the subsequent polymerization stage. Moreover, in this case, it is necessary to introduce so much cocatalyst into the prepolymerization stage in order to obtain a sufficient polymerization reaction therein.

[0118] It is to be understood that within the scope of the present invention the amount of polymer produced in the prepolymerisation is within 1.0 to 5.0 wt% relative to the final metallocene catalysed MDPE. This can be counted as part of the first polyethylene component (A).

[0119] catalyst

[0120] The metallocene-catalyzed MDPE of embodiment (I) of the present invention is MDPE prepared using a metallocene catalyst. The metallocene catalyst comprises a metallocene complex and a cocatalyst. The metallocene compound or complex is also referred to herein as an organometallic compound (C).

[0121] The organometallic compound (C) comprises a transition metal (M) from Groups 3 to 10 of the Periodic Table of Elements (IUPAC 2007) or from the actinides or lanthanides.

[0122] According to the present invention, the term "organometallic compound (C)" includes any metallocene or non-metallocene compound of a transition metal, which carries at least one organic (coordinating) ligand and exhibits catalytic activity alone or together with a cocatalyst. Transition metal compounds are well known in the art, and the present invention encompasses compounds of metals from Groups 3 to 10, e.g. Groups 3 to 7, or Groups 3 to 6, e.g. Groups 4 to 6, of the Periodic Table (IUPAC 2007), as well as lanthanides or actinides.

[0123] In one embodiment, the organometallic compound (C) has the following formula (I):

[0124]

[0125] Wherein each X is independently a halogen atom, C 1-6 -alkyl, C 1-6 - alkoxy, phenyl or benzyl;

[0126] Each Het is independently a monocyclic heteroaromatic group containing at least one heteroatom selected from O or S;

[0127] L is -R'2Si-, wherein each R' is independently a C substituted with an alkoxy group having 1 to 10 carbon atoms. 1-20 -Hydrocarbon or C 1-10 -alkyl;

[0128] M is Ti, Zr or Hf;

[0129] Each R 1 Same or different, is C 1-6 -alkyl or C 1-6 - alkoxy;

[0130] Each n is 1 to 2;

[0131] Each R 2 Same or different, is C 1-6 -alkyl, C 1-6 -alkoxy or -Si(R)3 group;

[0132] Each R is optionally replaced by 1 to 3 C 1-6 -alkyl substituted C 1-10 -alkyl or phenyl; and each p is 0 to 1.

[0133] Preferably, the compound of formula (I) has the structure

[0134]

[0135] Wherein each X is independently a halogen atom, C 1-6 -alkyl, C 1-6 -alkoxy, phenyl or benzyl; L is Me2Si-;

[0136] Each R 1 Same or different and C 1-6 - alkyl, for example methyl or tert-butyl;

[0137] Each n is 1 to 2;

[0138] R 2 is -Si(R)3alkyl; each p is 1;

[0139] Each R is C 1-6 -alkyl or phenyl.

[0140] Highly preferred complexes of formula (I) are

[0141]

[0142]

[0143] Most preferably, the complex dimethylsilanediylbis[2-(5-trimethylsilylfuran-2-yl)-4,5-dimethylcyclopentadien-1-yl]zirconium dichloride is used.

[0144] More preferably, the polyethylene components (A) and (B) of the metallocene-catalyzed MDPE are prepared using the same metallocene catalyst, ie in the presence of the same metallocene catalyst.

[0145] To form the catalyst, a cocatalyst, also called an activator, well known in the art is used. Cocatalysts containing Al or B are well known and can be used here. Preferably, an aluminoxane (such as MAO) or a boron-based cocatalyst (such as a borate) is used.

[0146] In contrast to Ziegler Natta catalysis, polyethylene copolymers produced using single-site catalysis have characteristics that distinguish them from Ziegler Natta materials. In particular, the comonomer distribution is more uniform. This can be shown using TREF or Crystaf techniques. Catalyst residues can also indicate the catalyst used. Ziegler Natta catalysts do not contain group (IV) metals such as Zr or Hf.

[0147] Implementation Plan (II)

[0148] The metallocene-catalyzed MDPE of embodiment (II) consists of:

[0149] (i) 30 to 70 wt% of a polyethylene component (X), relative to the total weight of MDPE, having a molecular weight of 920 to 950 kg / m 3 A density in the range of 0.01 to 2.0 g / 10 min and an MFR2 (190°C, 2.16 kg, ISO 1133); and

[0150] (ii) 30 to 70 wt% of a polyethylene component (Y) relative to the total weight of the MDPE, having a molecular weight of 920 to 960 kg / m 3 The invention relates to a polymer having a density in a range of 1000 Å and a MFR2 (190°C, 2.16 kg, ISO 1133) of 0.1 to 10.0 g / 10 min.

[0151] Thus, in the metallocene-catalyzed MDPE in this embodiment (II), the weight ratio of polyethylene component (X) to polyethylene component (Y) is in the range of 30:70 to 70:30, preferably 35:65 to 65:35, more preferably 40:60 to 60:40. In some embodiments, the ratio may be 35 to 50 wt% of polyethylene component (X) to 50 to 65 wt% of polyethylene component (Y), for example 40 to 50 wt% of component (X) to 50 to 60 wt% of component (Y), wherein the wt% values ​​are relative to the total weight of the metallocene-catalyzed MDPE.

[0152] In a particularly preferred embodiment the wt% values ​​of polyethylene components (X) and (Y) add up to at most 100%.

[0153] In this embodiment (II), the polyethylene components (X) and / or (Y) may be homopolymers or ethylene copolymers, preferably both components are ethylene copolymers.

[0154] Preferably, components (X) and (Y) consist of a single ethylene copolymer.

[0155] Preferred ethylene copolymers use α-olefins (e.g., C3-12 α-olefins) as comonomers. Examples of suitable α-olefins include 1-butene, 1-hexene, and 1-octene. 1-Butene is a particularly preferred comonomer.

[0156] More preferably, both polyethylene components (X) and (Y) are ethylene-1-butene copolymers.

[0157] The MFR2 of the polyethylene component (X) is preferably in the range of 0.05 to 1.5 g / 10 min, more preferably 0.1 to 1.0 g / 10 min, even more preferably 0.2 to 0.8 g / 10 min.

[0158] The density of the polyethylene component (X) is preferably in the range of 925 to 945 kg / m 3 , preferably 928 to 942 kg / m 3 , even more preferably 930 to 940 kg / m 3 within the range.

[0159] The MFR2 of the polyethylene component (Y) is preferably in the range of 0.5 to 6.0 g / 10 min, more preferably 0.8 to 4.0 g / 10 min, even more preferably 1.0 to 2.5 g / 10 min.

[0160] The density of the polyethylene component (B) is preferably in the range of 930 to 955 kg / m 3 , more preferably 935 to 950 kg / m 3 , even more preferably 938 to 945 kg / m 3 within the range.

[0161] The metallocene-catalyzed MDPE of embodiment (II) can be produced by polymerization using conditions that produce a multimodal (eg, bimodal) polymer product using a metallocene catalyst system, such as the metallocene catalyst system described for embodiment (I).

[0162] Therefore, the metallocene-catalyzed MDPE of embodiment (II) can be produced in a two-stage process, preferably comprising a slurry reactor (loop reactor), wherein the slurry (loop 1) reactor is connected in series with a gas phase reactor (reactor 2), thereby producing polyethylene component (X) or polyethylene component (Y) in loop reactor 1, and then producing the other ethylene polymer component in the presence of the first produced ethylene polymer component in loop reactor 2 to produce metallocene-catalyzed MDPE, preferably, polyethylene component (X) is produced in loop reactor 1, and polyethylene component (Y) is produced in loop reactor 2 in the presence of polyethylene component (X) to produce metallocene-catalyzed MDPE.

[0163] The first polymerization stage produces polyethylene component (X), which is subsequently fed to the second polymerization stage. The second polymerization stage produces polyethylene component (Y), thereby producing the metallocene-catalyzed MDPE of embodiment (II).

[0164] The first and second polymerisation stages are preferably slurry polymerisation steps.

[0165] Slurry polymerization is usually carried out in an inert diluent, which is usually a hydrocarbon diluent, such as methane, ethane, propane, n-butane, isobutane, pentane, hexane, heptane, octane, etc., or a mixture thereof. Preferably, the diluent is a low boiling hydrocarbon having 1 to 4 carbon atoms or a mixture of these hydrocarbons. A particularly preferred diluent is propane, which may contain small amounts of methane, ethane and / or butane.

[0166] The temperature of the first and second polymerization stages is generally from 60 to 100° C., preferably from 70 to 90° C. Excessively high temperatures should be avoided to prevent partial dissolution of the polymer into the diluent and contamination of the reactor. The pressure is from 1 to 150 bar, preferably from 40 to 80 bar.

[0167] Slurry polymerization can be carried out in any known reactor for slurry polymerization. Such reactors include continuous stirred tank reactors and loop reactors. Slurry polymerization is particularly preferably carried out in a loop reactor. In such a reactor, the slurry is circulated at high speed along a closed pipeline by using a circulating pump. Loop reactors are well known in the art, and examples are given, for example, in US-A-4582816, US-A-3405109, US-A-3324093, EP-A-479186 and US-A-5391654. Therefore, it is preferred to carry out the first and second polymerization stages in the form of slurry polymerization in two continuous loop reactors.

[0168] The slurry can be withdrawn from each reactor continuously or intermittently. A preferred mode for intermittent withdrawal is to use settling legs, wherein the slurry is concentrated and then a batch of concentrated slurry is withdrawn from the reactor. The use of settling legs is disclosed in US-A-3374211, US-A-3242150 and EP-A-1310295. Continuous withdrawal is disclosed in EP-A-891990, EP-A-1415999, EP-A-1591460 and WO-A-2007 / 025640. As disclosed in EP-A-1310295 and EP-A-1591460, continuous withdrawal is advantageously combined with a suitable concentration method. Preferably, the slurry is withdrawn continuously from each of the first and second polymerization stages.

[0169] Hydrogen is usually introduced into the first and second polymerisation stages for controlling the MFR2 of the first and second ethylene polymers. The amount of hydrogen required to achieve the desired MFR depends on the catalyst used and the polymerisation conditions.

[0170] The productivity is appropriately controlled by the catalyst feed rate. The productivity can also be influenced by appropriate selection of the monomer concentration. Then, by appropriate adjustment of the ethylene feed rate, the desired monomer concentration can be achieved.

[0171] Therefore, the metallocene-catalyzed MDPE according to embodiment (II) of the present invention is preferably produced in a loop-loop cascade.Such a polymerization step may be preceded by a prepolymerization step as described above for embodiment (I).

[0172] (II) Mixed plastics - polyethylene recycled blends (PERB)

[0173] In addition to the metallocene-catalyzed MDPE, the compositions of the present invention also include a mixed plastic-polyethylene recycled blend (PERB).

[0174] It is the essence of the present invention that the recycled blend is obtained from a post-consumer waste stream and / or a post-industrial waste stream, preferably from a post-consumer waste stream.

[0175] According to the present invention, the mixed plastic - polyethylene recycled blend (PERB) is typically a blend wherein at least 90 wt%, preferably at least 95 wt%, more preferably 100 wt% of the mixed plastic - polyethylene recycled blend (PERB) comes from post-consumer waste, such as from conventional collection systems (kerbside collection), such as that implemented in the EU, and / or from post-industrial waste, preferably from post-consumer waste.

[0176] The post-consumer waste can be identified by its limonene content.Preferably the post-consumer waste has a limonene content of 0.1 to 500 mg / kg.

[0177] The mixed plastic-polyethylene recycled blend (PERB) preferably comprises

[0178] A total amount of ethylene units (C2 units) of 80.0 wt% to 96.0 wt%, more preferably 82.5 wt% to 95.5 wt%, still more preferably 85.0 wt% to 95.5 wt%, most preferably 87.5 wt% to 95.0 wt%;

[0179] The total amount of continuous units having 3 carbon atoms corresponding to polypropylene (continuous C3 units) is 0.2 to 6.5 wt%, more preferably 0.4 to 6.0 wt%, still more preferably 0.6 to 5.5 wt%, most preferably 0.75 to 5.0 wt%.

[0180] Therefore, the total amount of C2 units and continuous C3 units is based on the total weight of the monomer units in the mixed plastic-polyethylene recycled blend (PERB) and is calculated according to the quantitative13 The results were measured by C{1H}NMR measurement.

[0181] In addition to C2 units and continuous C3 units, the mixed plastic-polyethylene recycled blend (B) may also include units having 3, 4, 6 or 7 or more carbon atoms, so that the mixed plastic polyethylene recycled blend (B) as a whole may include ethylene units and mixed units having 3, 4, 6 and 7 or more carbon atoms.

[0182] The mixed plastic-polyethylene recycled blend (PERB) preferably comprises any combination of one or more of the following, preferably all:

[0183] A total amount of 0.00 wt% to 0.50 wt%, more preferably 0.00 wt% to 0.40 wt%, still more preferably 0.00 wt% to 0.30 wt%, most preferably 0.00 wt% to 0.25 wt% of units having 3 carbon atoms as isolated units (isolated C3 units);

[0184] A total amount of 0.50 wt% to 5.00 wt%, more preferably 0.75 wt% to 4.00 wt%, still more preferably 1.00 wt% to 3.50 wt%, most preferably 1.25 wt% to 3.00 wt% of units having 4 carbon atoms (C4 units);

[0185] A total amount of 0.50 wt% to 7.50 wt%, more preferably 0.75 wt% to 6.50 wt%, still more preferably 1.00 wt% to 5.50 wt%, most preferably 1.25 wt% to 5.00 wt% of units having 6 carbon atoms (C6 units);

[0186] a total amount of 0.20 wt % to 2.50 wt %, preferably 0.30 wt % to 2.00 wt %, still more preferably 0.40 wt % to 1.5 wt %, most preferably 0.45 wt % to 1.25 wt % of units having 7 carbon atoms (C7 units), and

[0187] The content is 20.wt% to 65.0wt%, preferably 25.0wt% to 62.5wt%, more preferably 30.0wt% to 60.0wt%, most preferably 32.0wt% to 55.0wt% LDPE.

[0188] Therefore, the total amount of C2 units, the total amount of continuous C3 units, the total amount of isolated C3 units, the total amount of C4 units, the total amount of C6 units, the total amount of C7 units and the content of LDPE are based on the total weight of the monomer units in the mixed plastic-polyethylene recycled blend (B) and are quantitatively calculated according to 13 The results were measured by C{1H}NMR measurement.

[0189] Preferably, the total amount of units attributable to comonomers (i.e., separated C3 units, C4 units, and C6 units) in the mixed plastic-polyethylene recycled blend (PERB) is from 4.00 wt% to 20.00 wt%, more preferably from 4.50 wt% to 17.50 wt%, still more preferably from 4.75 wt% to 15.00 wt%, most preferably from 5.00 wt% to 12.50 wt%, and according to the quantitative 13 The measurement was carried out by C{1H}NMR measurement.

[0190] Preferably, the mixed plastic-polyethylene recycled blend (PERB) has

[0191] an MFR2 (ISO 1133, 2.16 kg, 190°C) of 0.1 to 1.2 g / 10 min, more preferably 0.3 to 1.1 g / 10 min; and / or

[0192] 910 to 945 kg / m 3 , more preferably 915 to 942 kg / m 3 , most preferably 918 to 940 kg / m 3 density.

[0193] The mixed plastic - polyethylene recycled blend (PERB) preferably does not contain carbon black. It is further preferred that the mixed plastic - polyethylene recycled blend (PERB) does not contain any pigment other than carbon black.

[0194] The mixed plastic - polyethylene recycled blend (PERB) is preferably a natural mixed plastic - polyethylene recycled blend (PERB).

[0195] Mixed plastics-polyethylene recycled blends (PERB) may also include:

[0196] 0 to 10 wt% of units derived from α-olefins,

[0197] 0 to 3.0 wt% stabilizer,

[0198] 0 to 3.0 wt% talc,

[0199] 0 to 3.0 wt% chalk,

[0200] 0 to 6.0 wt% of other components

[0201] All percentages are relative to the mixed plastic-polyethylene recycled blend (PERB).

[0202] The mixed plastic-polyethylene recycled blend (PERB) preferably has any combination of one or more of the following properties, more preferably all of them:

[0203] MFR5 (ISO 1133, 5.0 kg,

[0204] 190℃);

[0205] MFR of 20.0 to 50.0 g / 10 min, more preferably 25.0 to 45.0 g / 10 min 21 (ISO 1133, 21.6kg, 190℃);

[0206] 1.0 to 3.5 seconds -1 , more preferably 1.3 to 3.0s -1 The polydispersity index PI;

[0207] Shear thinning index SHI of 15 to 40, more preferably 20 to 35 2.7 / 210 ;

[0208] 500 to 750 Pa·s, more preferably 550 to 700 Pa·s, complex viscosity at a frequency of 300 rad / s, eta300;

[0209] A complex viscosity at a frequency of 0.05 rad / s, eta0.05, of 15000 to 30000 Pa·s, more preferably 15500 to 27500 Pa·s;

[0210] A strain hardening modulus, ie, SH modulus, of 12.5 to 20.0 MPa, more preferably 13.0 to 17.5 MPa.

[0211] It is preferred that the mixed plastic-polyethylene recycled blend (PERB) has a relatively low gel content, especially compared to other mixed plastic-polyethylene recycled blends.

[0212] The gel content of the mixed plastic-polyethylene recycled blend (PERB) with a size of gels above 600 μm to 1000 μm is preferably not more than 1000 gels / m 2 , more preferably no more than 850 gel / m 2 The lower limit of the gel content for gels with a size of 600 μm or more to 1000 μm is usually 100 gels / m 2 , preferably 150 gel / m 2 .

[0213] Furthermore, the gel content of the mixed plastic-polyethylene recycled blend (PERB) with gels having a size of 1000 μm or more is preferably not more than 200 gels / m 2 , more preferably no more than 150 gel / m 2The lower limit of gel content for gels with a size of 1000 μm or more is usually 10 gels / m 2 , preferably 14 gel / m 2 .

[0214] The mixed plastic-polyethylene blend (PERB) used herein is commercially available. One suitable recyclable is available, for example, from Ecoplast Kunststoffrecycling GmbH under the brand names NAV 101 and NAV 102.

[0215] As mentioned above, the polyethylene composition according to the present invention provides an improved balance between stiffness, impact resistance and optics (ie haze) for films comprising the blend.

[0216] The specific design of the metallocene catalyzed MDPE (MDPE) thus allows the addition of more recyclables, ie more than 50 wt% of the composition, and still provides a film with a good impact / stiffness / optical balance.

[0217] Therefore, the present invention further relates to a film comprising at least one layer comprising the composition described above.

[0218] membrane

[0219] The film of the present invention comprises at least one layer comprising a polyethylene composition as described above. The film may be a monolayer film comprising the polyethylene composition defined above or a multilayer film in which at least one layer comprises the polyethylene composition defined above. The terms "monolayer film" and "multilayer film" have well-known meanings in the art.

[0220] The film is preferably produced by any conventional film extrusion process known in the art, including cast film and blown film extrusion. Most preferably, the film is a blown film or cast film, especially a blown film. For example, blown film is produced by extruding through an annular die and blowing into a tubular film by forming bubbles, which burst between rollers after solidification. The film can then be cut, cut or converted (e.g., folded) as required. Traditional film production techniques can be used in this regard. If preferred blown film or cast film is a multilayer film, each layer is typically coextruded. The technician will know suitable extrusion conditions.

[0221] The film according to the present invention may be subjected to post-treatment processes such as surface modification, lamination or orientation processes, etc. Such orientation processes may be uniaxial (MDO) or biaxial orientation, wherein uniaxial orientation is preferred.

[0222] In another preferred embodiment, the film is non-oriented.

[0223] Preferred films according to the invention are monolayer blown films.

[0224] The thickness of the single-layer film of the present invention may be 20 to 120 μm, preferably 30 to 100 μm, and more preferably 35 to 80 μm.

[0225] The film preferably comprises at least 90 wt%, more preferably at least 95 wt%, even more preferably at least 99 wt% of the composition according to the invention, and more preferably still consists thereof.

[0226] The film according to the present invention has at least one or more or all of the following properties a) to c):

[0227] a) the film of the invention has a dart drop impact strength (DDI) measured on a 40 μm single layer test blown film according to ISO 7765-1:1988 of at least 60 g to at most 250 g, preferably 65 g to at most 200 g, more preferably 70 g to at most 150 g, and / or

[0228] b) the film according to the invention may also have a haze measured on a 40 μm test blown film according to ASTM D1003 of less than 22.0%, preferably in the range of 5.0 to 21.0%, more preferably 10.0 to 20.0%, even more preferably 12.0 to 17.0%, and / or

[0229] c) The films according to the invention have a good stiffness (in both directions) of > 150 MPa (according to ISO

[0230] 527-3 tensile modulus measured on 40 μm single layer test blown film).

[0231] Thus, the film comprising the polyethylene composition has a tensile modulus in machine direction (MD) and transverse direction (TD) of >150 MPa to 500 MPa, preferably 200 MPa to 400 MPa (measured according to ISO 527-3 on 40 μm monolayer test blown films).

[0232] d) In one embodiment of the present invention, according to formula (II):

[0233] The photomechanical ability (OMA) measured on a 40 μm test blown film is at least 1150 [MPa*g / %]

[0234] to at most 3000 [MPa*g / %], preferably in the range of 1200 [MPa*g / %] to at most 2500 [MPa*g / %], more preferably in the range of 1300 [MPa*g / %] to at most 2000 [MPa*g / %], wherein the tensile modulus in the longitudinal direction is measured at 23°C on a 40 μm test blown film according to ISO 527-3, DDI is the dart impact strength determined on a 40 μm test blown film according to ISO 7765-1:1988, and the haze is measured on a 40 μm test blown film according to ASTM D1003.

[0235] Preferably, the membrane according to the invention satisfies parameter d) and additionally at least parameter a), more preferably parameter d and additionally parameters a and b).

[0236] The films according to the invention are very suitable for use in a variety of packaging applications, in particular for secondary packaging which does not require food approval, or even for primary packaging of non-food products.

[0237] Furthermore, the film according to the invention can be used as a layer in a multilayer polyethylene-based blown film, preferably as a core layer in a multilayer polyethylene-based blown film.

[0238] The present invention will be further described with reference to the following non-limiting examples.

[0239] Determination method

[0240] Unless otherwise stated in the description or in the experimental section, the following methods were used to determine the properties of the polymers (including parts and components thereof) and / or any sample preparations thereof as described in the text or in the experimental section.

[0241] Melt flow rate:

[0242] The melt flow rate (MFR) is determined according to ISO 1133 and is expressed in g / 10 min. The MFR is an indicator of the flowability of the polymer and therefore of its processability. The MFR of polyethylene is determined at 190°C. The MFR can be determined at different loads, for example 2.16 kg (MFR2), 5 kg (MFR5) or 21.6 kg (MFR 21 ).

[0243] Calculation of MFR2 of component B and part (A-2)

[0244] logA=x·logB+(1-x)·logC

[0245]

[0246] For component B:

[0247] B = MFR2 of component (A)

[0248] C = MFR2 of component (B)

[0249] A = Final MFR2 of the multimodal polyethylene copolymer (P) (blend)

[0250] X = weight fraction of component (A).

[0251] For part (A-2):

[0252] B = MFR2 of the first part (A-1)

[0253] C = MFR2 of the second part (A-2)

[0254] A = Final MFR2 of cyclic polymer (= component (A)) (mixture)

[0255] X = weight fraction of the first part (A-1).

[0256] density

[0257] The density of polymers is measured according to ISO 1183 and is expressed in kg / m 3 Given, sample preparation was performed according to ISO 1872-2.

[0258] GPC

[0259] The average molecular weight (M z 、M w and M n ), molecular weight distribution (MWD) and its breadth described by the polydispersity index PDI = Mw / Mn (wherein Mn is the number average molecular weight and Mw is the weight average molecular weight) are calculated by gel permeation chromatography (GPC) according to ISO 16014-1:2003, ISO 16014-2:2003, ISO 16014-4:2003 and ASTM D 6474-12 using the following formula:

[0260]

[0261] For a constant elution volume interval ΔV i , where A i and M i and elution volume V i The associated chromatographic peak slice area and the polyolefin molecular weight (MW), where N equals the number of data points obtained from the chromatogram between the integration limits.

[0262] A high temperature GPC instrument equipped with an infrared (IR) detector (IR4 or IR5 from PolymerChar (Valencia, Spain)) and equipped with 3x Agilent-PLgel Olexis and 1x Agilent-PLgel Olexis Guard columns was used. 1,2,4-Trichlorobenzene (TCB) stabilized with 250 mg / L 2,6-di-tert-butyl-4-methylphenol was used as solvent and mobile phase. The chromatographic system was operated at a constant flow rate of 1 mL / min at 160°C. 200 μL of sample solution was injected for each analysis. Data collection was performed using Agilent Cirrus software version 3.3 or PolymerChar GPC-IR control software.

[0263] The column set was calibrated using universal calibration (according to ISO 16014-2:2003) with 19 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11500 kg / mol. The PS standards were dissolved at room temperature for several hours. The conversion of polystyrene peak molecular weight to polyolefin molecular weight was accomplished by using the Mark Houwink equation and the following Mark Houwink constants:

[0264] K PS =19x 10 -3 mL / g, α PS =0.655

[0265] K PE =39x 10 -3 mL / g, α PE =0.725

[0266] K PP =19x 10 -3 mL / g, α PP =0.725

[0267] A third-order polynomial fit was used to fit the calibration data.

[0268] All samples were prepared in the concentration range of 0.5-1 mg / ml and dissolved at 160°C for 2.5 hours for PP or 3 hours for PE with continuous gentle shaking.

[0269] Dart Drop Intensity (DDI): Determination of impact resistance by free falling dart method

[0270] DDI was measured according to ISO 7765-1:1988 / Method A on films (non-oriented films and laminates) produced as shown below. This test method covers the determination of the energy that will cause film failure under specified conditions of impact with a dart falling freely from a specified height, which will cause 50% of the test specimens to fail (Step Method A). A uniform increment of the missile mass was used during the test, and after each specimen test, the missile weight was reduced or increased by a uniform increment depending on the observed result (failure or no failure) of the specimen.

[0271] Standard conditions:

[0272] Adjustment time: >96h

[0273] Test temperature: 23℃

[0274] Dart head material: phenolic resin

[0275] Dart diameter: 38mm

[0276] Drop height: 660mm

[0277] result:

[0278] Impact failure weight - 50% [g]

[0279] Tensile modulus

[0280] The tensile modulus (E-Mod (MPa)) of film samples (prepared as described in Film Sample Preparation) was measured in the longitudinal and / or transverse directions according to ISO 527-3 with a film thickness of 40 μm and a crosshead speed of 1 mm / min.

[0281] Haze

[0282] The haze was measured according to ASTM D 1003-00 on the films produced as shown below.

[0283] The photomechanical ability (OMA) was determined for 40 μm test blown films and calculated according to formula (II):

[0284]

[0285] The longitudinal tensile modulus is measured at 23°C according to ISO 527-3, and the DDI is measured according to ISO

[0286] Dart impact strength was determined according to ASTM D7765-1:1988, and haze was measured according to ASTM D1003.

[0287] Quantification of C2, iPP (continuous C3), LDPE and polyethylene short chain branches in polyethylene-based recyclates

[0288] A Bruker Avance III 400 MHz NMR spectrometer was used to analyze the 1 H and 13 C was operated at 400.15 and 100.62 MHz and quantitative data were recorded in solution. 13 C{ 1 H}NMR spectra. All spectra were obtained using 13 C optimized 10 mm extended temperature probe was recorded at 125 °C, and nitrogen was used for all pneumatics. Approximately 200 mg of material was dissolved in 3 ml of 1,2-tetrachloroethane-d2 (TCE-d2) together with chromium (III) acetylacetonate (Cr(acac)3) to obtain a 65 mM solution of the relaxation agent in the solvent {singh09}. To ensure a homogeneous solution, the NMR tube was further heated in a rotary oven for at least 1 hour after initial sample preparation in a heat block. The tube was rotated at a frequency of 10 Hz during insertion into the magnet. This setup was chosen primarily for the high resolution and quantification required for accurate ethylene content quantification. Standard single pulse excitation without NOE was used, using an optimized tip angle, a recycle delay of 1 s, and a dual-level WALTZ16 decoupling scheme {zhou07, busico07}. A total of 6144 (6k) transients were acquired for each spectrum.

[0289] Quantitative 13 C{ 1 The H} NMR spectra were processed, integrated, and the relevant quantitative properties were determined from the integration using a proprietary computer program. All chemical shifts were indirectly referenced to the central methylene of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. Characteristic signals corresponding to polyethylene and polypropylene with different short chain branches (B1, B2, B4, B5, B6plus) were observed {randall89, brandolini00}.

[0290] Characteristic signals corresponding to the presence of polyethylene were observed, which contained isolated B1 branches (starB1 33.3ppm), isolated B2 branches (starB2 39.8ppm), isolated B4 branches (twoB4 23.4ppm), isolated B5 branches (threeB5 32.8ppm), all branches longer than 4 carbons (starB4plus 38.3ppm) and the third carbon from the end of a saturated aliphatic chain (3s 32.2ppm). The combined intensity of the ethylene backbone methine carbon (ddg) containing polyethylene backbone carbon (dd 30.0ppm), γ-carbon (g 29.6ppm), 4s and threeB4 carbon (compensated later) was between 30.9ppm and 29.3ppm, excluding Tββ from polypropylene. The amount of C2-related carbon was quantified using all mentioned signals according to the following equation:

[0291] f C2总计 =(Iddg-ItwoB4)+(IstarB1 * 6)+(IstarB2 * 7)+(ItwoB4 * 9)

[0292] +I(threeB5 * 10)+((IstarB4plus-ItwoB4-IthreeB5) * 7)+(I3s * 3)

[0293] Characteristic signals corresponding to the presence of polypropylene (iPP, continuous C3) were observed at 46.7 ppm, 29.0 ppm and 22.0 ppm. The amount of PP-related carbon was quantified using the integration of Sαα at 46.6 ppm:

[0294] f PP =Isαα * 3

[0295] The weight percentage of C2 fraction and polypropylene can be quantified according to the following equation:

[0296] wt C2部分 =fC C2总计 * 100 / (fC C2总计 +fC PP )

[0297] wt PP =fC PP * 100 / (fC C2总计 +fC PP )

[0298] Characteristic signals corresponding to the various short chain branches are observed and quantified as their weight percentage of the relevant branch will be the alpha olefin, first quantifying the weight fraction of each:

[0299] fwtC2=fC C2总计 -((IstarB1 * 3)-(IstarB2 * 4)-(ItwoB4 * 6)-(IthreeB5 * 7)

[0300] fwtC3 (separation C3) = IstarB1 * 3

[0301] fwtC4=IstarB2 * 4

[0302] fwtC6=ItwoB4 * 6

[0303] fwtC7=IthreeB5 * 7

[0304] Normalization of all weight fractions results in the quantity of weight percentages of all relevant branches:

[0305] fsum wt%总计 =fwtC2+fwtC3+fwtC4+fwtC6+fwtC7+fC PP

[0306] wtC2 total = fwtC2*100 / fsum wt%总计

[0307] wtC3 total = fwtC3*100 / fsum wt%总计

[0308] wtC4 total = fwtC4*100 / fsum wt%总计

[0309] wtC6 total = fwtC6*100 / fsum wt%总计

[0310] wtC7 total = fwtC7*100 / fsum wt%总计

[0311] The LDPE content can be estimated assuming that the B5 branches are almost constant in LDPE, which are produced only by ethylene polymerized in the high pressure process. We found that the average amount of B5, if quantified as C7, is 1.46 wt%. Based on this assumption, the LDPE content can be estimated to be within certain ranges (approximately between 20 wt% and 80 wt%), which depend on the SNR ratio of the three B5 signals:

[0312] wt% LDPE = wtC7 total * 100 / 1.46

[0313] References:

[0314] zhou07Zhou,Z.,Kuemmerle,R.,Qiu,X.,Redwine,D.,Cong,R.,Taha,A.,Baugh,D.Winniford,B.,J.Mag.Reson.187(2007)225.

[0315] busico07 Busico,V.,Carbonniere,P.,Cipullo,R.,Pellecchia,R.,Severn,J.,Talarico,G.,Macromol.Rapid Commun.2007,28,1128.

[0316] singh09 Singh,G.,Kothari,A.,Gupta,V.,Polymer Testing 28 5(2009),475.randall89 J.Randall,Macromol.Sci.,Rev.Macromol.Chem.Phys.1989,C29,201.brandolini00 AJBrandolini,DDHills,NMR Spectra of Polymers and PolymerAdditives,Marcel Dekker Inc.,2000.

[0317] Rheological measurements

[0318] Dynamic shear measurement (frequency sweep measurement)

[0319] Characterization of polymer compositions or melts of polymers by dynamic shear measurements as described above or below, in accordance with ISO standards 6721-1 and 6721-10. Measurements were performed on an Anton Paar MCR501 stress-controlled rotational rheometer equipped with 25 mm parallel plate geometry. Measurements were performed on compression molded plaques using a nitrogen atmosphere and setting the strain in the linear viscoelastic range. Oscillatory shear tests were performed at 190°C, using a frequency range between 0.01 and 600 rad / s, with a gap setting of 1.3 mm.

[0320] In dynamic shear experiments, the probe is subjected to uniform deformation under sinusoidally varying shear strain or shear stress (strain and stress controlled modes, respectively). In controlled strain experiments, the probe is subjected to a sinusoidal strain that can be expressed as

[0321] γ(t)=γ0 sin(ωt) (1)

[0322] If the applied strain is within the linear viscoelastic range, the resulting sinusoidal stress response can be given by

[0323] σ(t)=σ0 sin (ωt+δ) (2)

[0324] in

[0325] σ0 and γ0 are stress and strain amplitudes, respectively,

[0326] ω is the angular frequency

[0327] δ is the phase shift (loss angle between applied strain and stress response)

[0328] t is the time

[0329] Dynamic test results are usually expressed by several different rheological functions, namely shear storage modulus G', shear loss modulus G", complex shear modulus G * , complex shear viscosity η * , dynamic shear viscosity η', the out-of-phase component η" of the complex shear viscosity and the loss tangent tanδ can be expressed as follows:

[0330]

[0331] G * =G′+ iG″ [Pa] (5)

[0332] η * =η′-iη″ [Pa.s] (6)

[0333]

[0334] As described in Equation 9, the so-called shear thinning index is determined which is related to the MWD and independent of the Mw.

[0335]

[0336] For example, SHI (2.7 / 210) For G equal to 2.7 kPa * The value of the complex viscosity in Pa.s determined is divided by the value of G equal to 210 kPa * The value is defined by the complex viscosity in Pa.s.

[0337] The storage modulus (G'), loss modulus (G"), complex modulus (G * ) and complex viscosity (η * ) value.

[0338] So, for example, η* 300rad / s (eta * 300rad / s ) is used as an abbreviation for the complex viscosity at a frequency of 300 rad / s, η * 0.05rad / s (eta * 0.05rad / s ) is the abbreviation for the complex viscosity at a frequency of 0.05 rad / s.

[0339] The loss tangent, tan(δ), is defined as the ratio of the loss modulus (G") to the storage modulus (G') at a given frequency. Thus, for example, tan 0.05 Used as an abbreviation for the ratio of the loss modulus (G") to the storage modulus (G') at 0.05 rad / s, tan 300 Used as an abbreviation for the ratio of loss modulus (G") to storage modulus (G') at 300 rad / s.

[0340] Elastic balance tan 0.05 / tan 300 Defined as loss tangent tan 0.05 and loss tangent tan 300 ratio.

[0341] In addition to the above rheological functions, other rheological parameters can also be determined, such as the so-called elastic index EI(x). The elastic index EI(x) is determined from the value of the storage modulus (G') for a value of x kPa of the loss modulus (G") and can be described by Eq. 10.

[0342] EI(x)=G′ for (G″=x kPa)[Pa] (10)

[0343] For example, EI(5 kPa) is defined by the value of the storage modulus (G') for a value of G" equal to 5 kPa.

[0344] The polydispersity index PI is defined by Eq. 11.

[0345]

[0346] where ω COP is the crossover angular frequency, determined as the angular frequency at which the storage modulus G' is equal to the loss modulus G".

[0347] These values ​​were determined by a single-point interpolation procedure defined in the Rheoplus software. In cases where a given G* value was not reached experimentally, it was determined by extrapolation using the same procedure as before. In both cases (interpolation or extrapolation), the options "Interpolate y-values ​​of parameter to x-values" and "Logarithmic interpolation type" in Rheoplus were applied.

[0348] References:

[0349] [1]Rheological characterization of polyethylene fractions” Heino, EL, Lehtinen, A., Tanner J., J., Neste Oy, Porvoo, Finland, Theor.Appl.Rheol., Proc.Int.Congr.Rheol, 11th (1992), 1, 360-362.

[0350] [2]The influence of molecular structure on some rheologicalproperties of polyethylene", Heino, EL, Borealis Polymers Oy, Porvoo, Finland, Annual Transactions of the Nordic Rheology Society, 1995.).

[0351] [3]Definition of terms relating to the non-ultimate mechanicalproperties of polymers,Pure&Appl.Chem.,Vol.70,No.3,pp.701-754,1998.

[0352] Strain Hardening (SH) Modulus

[0353] The strain hardening test is a modified tensile test performed at 80°C on specially prepared thin specimens. Strain Hardening Modulus (MPa) <gp>It is based on the true strain-true stress curve; calculated by using the slope of the curve in the true strain λ range (between 8 and 12).

[0354] The true strain λ is calculated from the length l (mm) and the gauge length l0 (mm), as shown in Equation 1.

[0355]

[0356] Where Δl is the increase in specimen length between gauge marks (mm). The true stress σtrue (MPa) is calculated according to Equation 2, assuming that the volume between gauge marks is conserved:

[0357] σ 真 =σ n λ (2)

[0358] where σ n is the engineering stress.

[0359] The Neo-Hookean constitutive model (Eq. 3) is used to fit the true strain-true stress data, from which the <gp>(MPa).

[0360]

[0361] where C is a mathematical parameter of the constitutive model describing the yield stress extrapolated to λ=0.

[0362] Five samples were initially measured. If <gp>If the coefficient of variation is greater than 2.5%, measure two additional specimens. If the test bar is strained in the fixture, the test result is rejected.

[0363] The PE pellets of the material were pressed into sheets of 0.30 mm thickness according to the pressing parameters provided in ISO 17855-2.

[0364] After the sheet is pressed, the sheet is annealed to remove any orientation or thermal history and maintain an isotropic sheet. The sheet is annealed in an oven at (120 ± 2) ° C for 1 hour, then the temperature chamber is closed and slowly cooled to room temperature. During this operation, the sheet is allowed to move freely.

[0365] Next, test pieces were punched out of the pressed sheets. A modified specimen geometry of ISO 37:1994 type 3 (Figure 3, according to ISO 37:1994) was used.

[0366] The specimens have a large clamping area to prevent the clamps from slipping, and the dimensions are shown in Table A.

[0367] Table A: Modified ISO 37:1994 Class 3 Dimensions

[0368] size Size(mm) L Starting length between clamps 30.0+ / -0.5 l0 Gauge length 12.5+ / -0.1 l1 Prism length 16.0+ / -1.0 l3 Overall length 70 R1 radius 10.0+ / -0.03 R2 radius 8.06+ / -0.03 b1 Prism width 4.0+ / -0.01 b2 Fixture width 20.0+ / -1.0 h thickness 0.30+0.05 / 0.30-0.03

[0369] The stamping procedure shall be performed in such a way that no deformations, cracks or other irregularities are present in the test piece.

[0370] The thickness of the sample was measured at three points on parallel areas of the sample; the lowest thickness measurement of these measurements was used for data processing.

[0371] 1. The following procedure is performed on a general purpose tensile testing machine with a controlled temperature chamber and a non-contact extensometer:

[0372] 2. Treat the sample in a temperature chamber at (80±1)℃ for at least 30 minutes before starting the test.

[0373] 3. Clamp the specimen on the upper side.

[0374] 4. Close the temperature chamber.

[0375] 5. After the temperature reaches (80±1)℃, close the lower clamp.

[0376] 6. Equilibrate the sample between the clamps for 1 minute before applying the load and starting the measurement.

[0377] 7. Add a preload of 0.5N at a speed of 5mm / min.

[0378] 8. Extend the specimen along its major axis at a constant transverse speed (20 mm / min) until the specimen breaks.

[0379] During the test, a 200N load cell was used to measure the load on the specimen. A non-contact extensometer was used to measure the elongation.

[0380] Gel content

[0381] The gel count was measured using a gel count device consisting of a measuring extruder ME 25 / 5200V1, 25*25D, an adapter and a slot die (opening 0.5*150 mm) with five temperature regulation zones adjusted to a temperature profile of 170 / 180 / 190 / 190 / 190° C. Attached to it was a cooling roll unit (13 cm diameter, temperature setting 50° C.), a line camera (CCD 4096 pixels for dynamic digital processing of grayscale images) and a winding unit.

[0382] For gel count content measurement, the material was extruded at a screw speed of 30 revolutions per minute, a draw speed of 3-3.5 m / min and a chill roll temperature of 50° C. to produce a thin cast film with a thickness of 70 μm and a width of approximately 110 mm.

[0383] The camera resolution on the membrane was 25 μm x 25 μm. The camera was operated in transmission mode with constant gray value (automatically set margin level = 170). The system was able to decide between 256 gray values ​​from black = 0 to white = 256. For the detection of gels, a sensitivity level dark of 25% was used. For each material, the line scan camera was used to check the 2 The average number of gel spots on the membrane surface area. The line scan camera is set to distinguish the size of the gel spots according to the following:

[0384] Gel size (size of the longest dimension of the gel)

[0385] 300μm to 599μm

[0386] 600μm to 999μm

[0387] Above 1000μm

[0388] Membrane sample preparation

[0389] A Collin 30 laboratory scale monolayer blown film line was used to prepare test films with a thickness of 40 μm consisting of the composition of the present invention and the respective comparative compositions. The film samples were produced at 194° C., a blow ratio of 1:2.5, and a frost line distance of 120 mm.

[0390] Blending is carried out directly on the film extrusion line.

[0391] Example:

[0392] Materials used:

[0393] Use NAV 101 as a mixed plastic polyethylene recycled blend (PERB).

[0394] NAV 101 is a low density polyethylene (LDPE) post-consumer recyclate blend available from Ecoplast Kunststoffrecycling GmbH. The properties of NAV 101 are shown in Table B.

[0395] Table B: Properties of NAV 101

[0396] Ethylene content (wt%) 90.67 Separation C3 content (wt%) 0 C4 content (wt%) 2.23 C6 content (wt%) 2.73 C7 content (wt%) 0.48 iPP content (wt%) 3.89 LDPE content (wt%) 33.00 <![CDATA[Density (kg / m 3 )]]> 923.9 <![CDATA[MFR2(g / 10min)]]> 1.02 <![CDATA[MFR5(g / 10min)]]> 3.57 <![CDATA[MFR 21 (g / 10min)]]> 41.56 SHI2.7 / 210 22.16 eta0.05(Pa·s) 16187 eta300(Pa·s) 618 PI(s-1) 1.46 SH modulus (MPa) 14.3 <![CDATA[Gel content (>1000μm) (1 / m 2 )]]> 16.9 <![CDATA[Gel content (600 - 1000 μm) (1 / m 2 )]]> 175.1 <![CDATA[Gel content (300 - 599) (μm / 1m 2 )]]> 885.9

[0397] Mixed partner of comparative example CE2

[0398] Lumicene Supertough 40ST05 (40ST05), available from Total, is a metallocene MDPE with a density of 940 kg / m 3 , MFR2 is 0.5g / 10min.

[0399] Catalyst Example: Preparation of Catalyst CAT1 for Examples IE1 and IE2 of the Present Invention and Comparative Example CE1:

[0400] SiO2 loading:

[0401] 10 kg of silica (PQ Corporation ES757, calcined at 600°C) was added from a feed bucket and inerted in the reactor until the O2 level reached less than 2 ppm.

[0402] Preparation of MAO / tol / MC:

[0403] At 25°C (oil circulation temperature) and 95rpm stirring, a 30wt% MAO toluene solution (14.1kg) was added from a balance to another reactor, followed by toluene (4.0kg). After adding toluene, the stirring speed was increased from 95rpm to>200rpm, with a stirring time of 30 minutes. Metallocene racemic-dimethylsilanediylbis{2-(5-(trimethylsilyl)furan-2-yl)-4,5-dimethylcyclopentadiene-1-yl}zirconium dichloride 477g was added from a metal cylinder, followed by 4kg toluene rinse (total toluene was 8.0kg). The reactor stirring speed was changed to 95rpm for MC feeding, returned to 200rpm and continued for 3h reaction time. After the reaction time, the MAO / tol / MC solution was transferred to a feed container.

[0404] Preparation of catalyst:

[0405] The reactor temperature was set to 10°C (oil circulation temperature) and stirring was adjusted to 40 rpm during the addition of MAO / tol / MC. MAO / tol / MC solution (22.2 kg) was added over 205 min, followed by a stirring time of 60 min (oil circulation temperature set to 25°C). After stirring, the "dry mix" was stabilized at 25°C (oil circulation temperature) for 12 h with a stirring speed of 0 rpm. The reactor was rotated 20° (back and forth) and stirred several times per hour at a speed of 5 rpm.

[0406] After stabilization, the catalyst was dried at 60°C (oil circulation temperature) for 2 h under a 2 kg / h nitrogen flow, followed by drying under vacuum for 13 h (same nitrogen flow rate, stirring at 5 rpm). The dried catalyst was sampled and the HC content was measured using a Sartorius moisture analyzer (model MA45) in a glove box using thermogravimetry. The target HC level was <2% (actual 1.3%).

[0407] polymerization:

[0408] IE1: Borstar pilot plant with three reactors (Loop 1-Loop 2-GPR1) and prepolymerization loop reactor. (MDPE-1)

[0409] IE2: Borstar pilot plant with two reactors (loop 2-loop 2) and prepolymerization loop reactor. (MDPE-2)

[0410] CE1: Borstar pilot plant with three reactors (Loop 1-Loop 2-GPR1) and prepolymerization loop reactor. (HPDE-1)

[0411] The polymerization conditions given in Table 1 were used to produce MDPE-1, MDPE-2 and HDPE-1.

[0412] Table 1: Polymerization conditions of MDPE-1, MDPE-2 and HDPE-1

[0413]

[0414]

[0415] The polymer was mixed with 0.05 wt% Irganox 1010 (BASF), 0.2 wt% Irgafos 168 (BASF) and 0.05 wt% CEASIT FI (Baerlocher) calcium stearate, compounded and extruded on a ZSK 57 twin-screw extruder, where the wt% is relative to the total weight of the composition (total of polymer powder + additives = 100%). The melt temperature was 210° C. and the production rate was 200 kg / h.

[0416] Table 2: Material properties of MDPE-1, MDPE-2, HDPE-1 and 40ST05,

[0417] Material MDPE-1 MDPE-2 HDPE-1 40ST05 <![CDATA[MFR2 (g / 10 min) (Final)]]> 0.60 0.70 0.86 0.50 <![CDATA[MFR 21 (g / 10min)]]> 31.6 20.9 27.7 22.1 <![CDATA[MFR 21 / MFR2(FRR)]]> 52.6 29.9 32.2 44.2 <![CDATA[Density (kg / m 3 )]]> 940.4 937.7 957.6 940.0 Mz(g / mol) 318500 274000 313500 214500 Mw(g / mol) 110000 113500 108500 99750 Mn(g / mol) 17400 33187 24450 26150 Mz / Mw 2.9 2.41 2.89 2.15 Mw / Mn(MW) 6.3 3.42 4.44 3.81 FRR / (Mz / Mw) 18.1 12.4 11.1 20.6 FRR / MWD 8.3 8.7 7.3 11.6

[0418] Single layer blown film

[0419] The MDPE prepared above (respectively the polymer used for the comparative example) was blended with NAV 101 directly on the film extrusion line.

[0420] The following membranes were prepared using the above method (Membrane Sample Preparation).

[0421] Table 3: Composition and properties of blown films

[0422]

[0423]

[0424] As can be seen from Table 3 above, the composition using the metallocene-catalyzed MDPE according to the present invention shows the best balance between stiffness, impact resistance and optics (i.e. haze). This leads to significantly improved overall performance, i.e. the OMA of the film comprising the composition according to the present invention is improved compared to the comparative example.

[0425] CE1 is based on HDPE and therefore has good stiffness, but significantly poorer impact resistance, resulting in poorer overall performance.

[0426] CE2 is based on MDPE, which offers similar stiffness to IE1 and IE2, but has inferior DDI and haze, so the overall performance is significantly lower.< / gp> < / gp> < / gp>

Claims

1. A composition comprising: (I) 1.0 to 49.0 wt% of a metallocene-catalyzed medium density polyethylene (MDPE), based on the total weight of the composition, wherein the metallocene-catalyzed MDPE has 932 to 955 kg / m 3 Density within range (ISO 1183); MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 0.1 to 2.0 g / 10 min, MFR in the range of 10.0 to 40.0 g / 10 min 21 (190℃, 21.6kg, ISO 1133), MFR in the range of 20.0 to 60.0 21 / MFR2 ratio (FRR) Mw / Mn (MWD) in the range of 2.5 to 7.0, and FRR / MWD ratio in the range of 7.5 to 11.0; and (II) 51.0 to 99.0 wt% of a mixed plastic-polyethylene recycled blend (PERB), based on the total weight of the composition, having 0.1 to 1.2 g / 10min MFR2 (ISO 1133, 2.16 kg, 190°C), 910 to 945 kg / m 3 The density of 80.0 to 96.0 wt% of the total amount of ethylene units (C2 units) measured by NMR of the d2 tetrachloroethylene soluble fraction, The total amount of C2 units is based on the total weight of the monomer units in the mixed plastic-polyethylene blend (B) and is calculated according to the quantitative 13 C{1H}NMR measurement method is used to measure, The components (I) and (II) of the composition together constitute up to 100 wt%.

2. The composition of claim 1, wherein the metallocene-catalyzed MDPE has 933 to 950 kg / m 3 , preferably 935 to 945 kg / m 3 Density within the range (ISO 1183) and / or an MFR2 (190°C, 2.16 kg, ISO 1133) of a metallocene-catalyzed MDPE in the range of 0.2 to 1.5 g / 10 min, preferably 0.3 to 1.2 g / 10 min, more preferably 0.4 to 1.0 g / 10 min, and / or MFR in the range of 15 to 38.0 g / 10 min, preferably in the range of 18.0 to 35.0 g / 10 min, more preferably in the range of 20.0 to 33.0 g / 10 min 21 (190°C, 21.6kg, ISO 1133), and / or Flow rate ratio (FRR), MFR in the range of 22.0 to 58.0, preferably 25.0 to 55.0 21 / MFR2, and / or Molecular weight distribution (MWD), Mw / Mn, in the range of 2.8 to 6.8, preferably 3.0 to 6.5, and / or FRR / MWD ratio in the range of 7.8 to 10.5, preferably 8.0 to 10.

0.

3. The composition according to claim 1 or 2, wherein the metallocene-catalyzed MDPE has one or more or preferably all of the following properties: The weight average molecular weight Mw is at least 100000 g / mol, preferably in the range of 109000 to 150000 g / mol, more preferably 109000 to 130000 g / mol, still more preferably 1090000 to 120000 g / mol, and / or The z-average molecular weight Mz is between 215000 and 400000 g / mol, preferably between 230000 and 380000 g / mol, More preferably in the range of 250000 to 350000 g / mol, and / or The Mz / Mw ratio is in the range of 2.0 to 4.0, preferably 2.2 to 3.5, more preferably 2.3 to 3.2, and / or The FRR / (Mz / Mw) ratio is in the range of 11.5 to 20.0, preferably 11.8 to 19.0, more preferably 12.0 to 18.

5.

4. The composition according to any one of the preceding claims 1 to 3, wherein the metallocene-catalyzed MDPE comprises at least (i) 30 to 70 wt% of a polyethylene component (A) relative to the total weight of the MDPE, having a molecular weight of 950 to 980 kg / m 3 In the range of 955 to 975 kg / m 3 , more preferably 960 to 972 kg / m 3 , Even more preferably 962 to 970 kg / m 3 The density within the range, and 2 to 500 g / 10 min, preferably 10 to 400 g / 10 min, more preferably 50 to 300 g / 10 min, Even more preferably an MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 100 to 200 g / 10 min; and (ii) 30 to 70 wt% of a polyethylene component (B), relative to the total weight of the MDPE, having a molecular weight of 900 to 925 kg / m 3 , preferably 905 to 920 kg / m 3 , more preferably 908 to 918 kg / m 3 , even more preferably 910 to 916 kg / m 3 The density in the range of and 0.0001 to 1.0 g / 10 min, preferably 0.0005 to 0.8, more preferably 0.001 to 0.5 g / 10 min, Even more preferably polyethylene with an MFR2 (190°C, 2.16 kg, ISO 1133) of 0.002 to 0.1 g / 10 min; The polyethylene component (A) is preferably an ethylene homopolymer, and the polyethylene component (B) is preferably an ethylene-1-hexene copolymer.

5. The composition according to claim 4, wherein the polyethylene component (A) is an ethylene homopolymer mixture, the ethylene homopolymer mixture comprising, preferably consisting of, a first ethylene homopolymer fraction (A-1) and a second ethylene homopolymer fraction (A-2), wherein the ethylene polymer fraction (A-1) has MFR2 (190°C, 2.16 kg, 40.4 mmol / l) in the range of 5.0 to 100.0 g / 10 min, preferably 10.0 to 80.0 g / 10 min, more preferably 15.0 to 50.0 g / 10 min, even more preferably 20.0 to 40.0 g / 10 min ISO 1133), and 945 to 970 kg / m 3 , preferably 950 to 965 kg / m 3 , more preferably 952 to 962 kg / m 3 density within the range; and The ethylene polymer portion (A-2) has an MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 100.0 to 1500.0 g / 10 min, preferably 200.0 to 1200.0 g / 10 min, more preferably 300.0 to 1000.0 g / 10 min, most preferably 500.0 to 800.0 g / 10 min, and 960 to 980 kg / m 3 , preferably 965 to 980 kg / m 3 , more preferably 970 to 978 kg / m 3 Density within the range.

6. The composition according to any one of the preceding claims 1 to 3, wherein the metallocene-catalyzed MDPE consists of: (i) 30 to 70 wt% of a polyethylene component (X), relative to the total weight of MDPE, having a molecular weight of 920 to 950 kg / m 3 In the range of 925 to 945 kg / m 3 , more preferably 928 to 942 kg / m 3 , Even more preferably 930 to 940 kg / m 3 The density within the range, and 0.01 to 2.0 g / 10 min, preferably 0.05 to 1.5 g / 10 min, more preferably 0.1 to 1.0 g / 10 min, Even more preferably an MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 0.2 to 0.8 g / 10 min; and (ii) 30 to 70 wt% of a polyethylene component (Y) relative to the total weight of the MDPE, which is a polyethylene component having a molecular weight of 920 to 960 kg / m 3 , preferably 930 to 955 kg / m 3 , more preferably 935 to 950 kg / m 3 , even more preferably 938 to 945 kg / m 3 The density in the range of 0.1 to 10.0 g / 10 min, preferably 0.5 to 6.0 g / 10 min, more preferably 0.8 to 4.0 g / 10 min, Even more preferred are polyethylenes having an MFR2 (190°C, 2.16 kg, ISO 1133) of 1.0 to 2.5 g / 10 min, wherein both polyethylene components (X) and (Y) are preferably ethylene-1-butene copolymers.

7. The composition according to any one of the preceding claims, wherein the mixed plastic-polyethylene recycled blend (PERB) comprises ethylene units (C2 units) in a total amount of 80.0 wt% to 96.0 wt%, more preferably 82.5 wt% to 95.5 wt%, still more preferably 85.0 wt% to 95.5 wt%, most preferably 87.5 wt% to 95.0 wt%; The total amount is 0.2 wt% to 6.5 wt%, more preferably 0.4 wt% to 6.0 wt%, and still more preferably 0.6 wt% % to 5.5 wt%, most preferably 0.75 wt% to 5.0 wt% of continuous units with 3 carbon atoms corresponding to polypropylene (continuous C3 units); the total amount of C2 units and the total amount of continuous C3 units are based on the total weight of the monomer units in the mixed plastic-polyethylene recycled blend (PERB) and according to the quantitative 13 C{ 1 H}NMR measurement method.

8. The composition according to any one of the preceding claims, wherein the mixed plastic-polyethylene recycled blend (PERB) preferably comprises any combination of one or more of the following, preferably all: A total amount of 0.00 wt% to 0.50 wt%, more preferably 0.00 wt% to 0.40 wt%, still more preferably 0.00 wt% to 0.30 wt%, most preferably 0.00 wt% to 0.25 wt% of units having 3 carbon atoms as isolated units (isolated C3 units); A total amount of 0.50 wt% to 5.00 wt%, more preferably 0.75 wt% to 4.00 wt%, still more preferably 1.00 wt% to 3.50 wt%, most preferably 1.25 wt% to 3.00 wt% of units having 4 carbon atoms (C4 units); A total amount of 0.50 wt% to 7.50 wt%, more preferably 0.75 wt% to 6.50 wt%, still more preferably 1.00 wt% to 5.50 wt%, most preferably 1.25 wt% to 5.00 wt% of units having 6 carbon atoms (C6 units); The total amount is 0.20 wt% to 2.50 wt%, preferably 0.30 wt% to 2.00 wt%, and more preferably 0.40 wt% to 1.5 wt%, most preferably 0.45 wt% to 1.25 wt% of units having 7 carbon atoms (C7 units), and % LDPE; the total amount of C2 units, the total amount of continuous C3 units, the total amount of isolated C3 units, the total amount of C4 units, the total amount of C6 units, the total amount of C7 units and the content of LDPE are based on the total weight of the monomer units in the mixed plastic-polyethylene recycled blend (PERB) and according to the quantitative 13 C{ 1 H} NMR measurement method to measure or calculate.

9. The composition according to any one of the preceding claims, wherein the mixed plastic-polyethylene recycled blend (PERB) has MFR2 (ISO 1133, 2.16 kg, 190°C) in the range of 0.3 to 1.1 g / 10 min; and / or 915 to 942 kg / m 3 , preferably 918 to 940 kg / m 3 Density within the range.

10. A composition according to any one of the preceding claims, wherein the composition consists of: (I) 10.0 to 45.0 wt%, preferably 20.0 to 40.0 wt% of a metallocene-catalyzed medium density polyethylene (MDPE), and (II) 55.0 to 90.0 wt%, preferably 60.0 to 80.0 wt% of mixed plastics - polyethylene recycled blend (PERB).

11. A film comprising the composition according to any one of the preceding claims 1 to 10, wherein the film preferably comprises at least 90 wt%, more preferably at least 95 wt%, even more preferably at least 99 wt% of the composition, yet more preferably consists of the composition.

12. The film according to claim 11, wherein the film has at least one or more or preferably all of the following properties a) to c): a) a dart drop impact strength (DDI) of at least 60 g to at most 250 g, preferably 65 g to at most 200 g, more preferably 70 g to at most 150 g, measured according to ISO 7765-1:1988 on a 40 μm single layer test blown film, and / or b) less than 22.0%, preferably between 5.0 and 21.0%, more preferably between 10.0 and 20.0%, even more preferably A haze measured on a 40 μm test blown film according to ASTM D1003 in the range of 12.0 to 17.0%, and / or c) in the machine direction (MD) in the range of >150 MPa to 500 MPa, preferably 200 MPa to 400 MPa and tensile modulus in the transverse (TD) direction (measured according to ISO 527-3 on 40 μm single-layer test blown films).

13. The film according to claim 11, wherein d) of the film is according to formula (II): The photomechanical ability (OMA) measured on a 40 μm test blown film is at least 1150 [MPa*g / %] to at most 3000 [MPa*g / %], preferably in the range of 1200 [MPa*g / %] to at most 2500 [MPa*g / %], more preferably in the range of 1300 [MPa*g / %] to at most 2000 [MPa*g / %], wherein The tensile modulus in the machine direction is measured according to ISO 527-3 at 23°C on a 40 μm test blown film, the DDI is the dart drop impact strength determined according to ISO 7765-1:1988 on a 40 μm test blown film, and the haze is measured according to ASTM D1003 on a 40 μm test blown film.

14. The membrane according to claim 11, wherein the membrane satisfies parameter d) according to claim 13 and additionally at least parameter a) according to claim 12, more preferably satisfies parameter d) according to claim 13 and additionally parameters a) and b) according to claim 12.

15. Use of the film according to any of the preceding claims 11 to 14 as packaging material, in particular for secondary packaging not requiring food approval or for primary packaging of non-food products.

Citation Information

Patent Citations

  • Apparatus and method for producing ethylene polymer

    EP0479186A2

  • High solids slurry polymerization

    EP0891990A2

  • Polymerisation reactor

    EP1310295A1

  • Process and apparatus for producing olefin polymers

    EP1415999A1

  • Process for producing polyethylene

    EP1591460A1